Study of shear resistance and anisotropy of layered shales. - Min Gao; Bin Gong; Zhengzhao Liang; Shanpo Jia; Xianhui Feng (PLoS ONE)
Characterizing anisotropy remains challenging in rock mechanics. Particularly, the strengths and failure patterns of layered shales under shear load are significantly anisotropic mainly because of the bedding planes. Meanwhile, understanding the creation and propagation of shear fractures is critical for drilling, mining, tunnelling, exploitation of shale gas, etc. In this study, the shear resistance of layered shales is comprehensively investigated based on the direct shear tests numerically. The results show that the shear parameters are greatly affected by the anisotropy induced by the normal stress and orientation of bedding planes; the shear strength, cohesion and internal friction angle generally increase with the growth of bedding plane orientation. Furthermore, three shear failure patterns are summarized, i.e., (1) the shear failure along bedding planes; (2) the shear failure crossing bedding planes; (3) the combination of tensile failure along bedding planes and shear failure crossing bedding planes. Besides, the empirical fitting formula characterizing the shear strength of layered rocks under triaxial compression is provided, and the modified Mohr-Coulomb criterion reflecting rock anisotropy is proposed.